Isolation and Identification of Lactic Acid Bacteria (LAB) Producing Bacteriosin-Like from Smoked Giant Catfish (Arius Thalassinus) - Tita Rialita; Sumanti Debby Moody; Edy Subroto; Heditia Febby Susanto (Universitas Djuanda, 2021)
Bacteriocin was bacterial metabolite that have antimicrobial properties, so it had the potential to be used as food bio preservatives. Bacteriocin was produced by lactic acid bacteria (LAB), one of the sources of which was from smoked fish products. Some regions in Indonesia produce various types of smoked fish from various types of fish, which were thought to contain bacteriocin-producing lactic acid; one of them was giant cathfish (Arius thalassinus). This study aims to obtain LAB isolates that have strong antimicrobial activity and have the potential to produce bacteriocin-like from smoked giant catfish (Arius thalassinus). The research method used an experimental method that analyzed descriptively. Based on the results, there were 15 isolates LAB isolated from smoked giant catfish. Three selected isolates showed strong antimicrobial activity inhibiting E. coli and S. aureus bacteria, and the most effective inhibiting Salmonella sp. One selected LAB isolates identified Pediococcus acidilactici suspected to produce pediocin bacteriocin-like, while the other two isolates identified Lactobacillus plantarum sp 1 and Lactobacillus plantarum sp 2 which suspected to produce plantaricin bacteriocin. Bacteriocin from the three isolates of LAB had characteristics stable to temperatures up to 121oC, stable in pH range 2-6, and bacteriocin activity increased with the addition of SDS (Sodium Dodecyl Sulfate) and EDTA (Ethylenediaminetetraacetic acid) surfactants. The conclusion was that the bacteriocin produced was stable at high temperature, low pH, and resistence in the presence of surfactants, so it had the potential to be developed as biopreservatives material in preserving fish-based foods